The future of skin tightening: Mechanical or biological?. Issue 4 (3rd November 2020) - Duncan, Diane I.
Abstract: Introduction: Not too long ago, the concept of nonexcisional skin tightening was a field of dreams. Currently, the field of nonexcisional skin tightening is heavily device dependent. Though great strides have been made in both minimally invasive skin tightening and totally noninvasive devices, will these be in use for decades? Advances in biological research and development have been rapid. Consumer demand for regenerative solutions is high, despite the warnings from the Food and Drug Administration (FDA) noting that benefits are unproven and that instances of charlatan practice are high. While genetic modification of food is frowned upon, the use of biomarkers in medicine has become a standard of care. Energy based devices: Current devices that have retained value in the skin tightening arena include transcutaneous radiofrequency (RF) and microfocused ultrasound. Laser resurfacing can improve mild skin laxity but its best use is wrinkle removal and pigment and textural improvement. RF‐based subdermal tightening consistently achieves a higher measured skin surface contraction than alternatives such as ultrasound‐assisted or laser‐assisted liposuction. High‐intensity electromagnetic field (HIFEM) improves that framework that supports the overlying skin, as well as reducing diastasis recti. HIFEM can generate a 17.9% skin surface area contraction. A combination of transcutaneous RF and targeted pressure energy significantly reduces skin surface irregularities, cellulite, and striae while measurably thickening the dermis. Injectables and biologiocals: Biologically based entries into the field include mechanically processed adipose‐derived stem cells, nanofat, and exosomes. Intradermal injection of nanofat and topical application of exosomes following microneedling can "resurface" skin by reversing many age related changes. A recently approved collagense drug can correct skin surface depressions such as cellulite, deformities following liposuction, and other areas of fibrosis. Conclusion: Surgical skin excision has largely been replaced with minimally invasive and noninvasive alternatives. While energy based devices still dominate this field, biologicals are rapidly gaining ground. Substances that induce cell signaling can target cell senescence. The future of skin tightening will include treatment options that offer tightening, smoothing, dermal thickness improvement, hydration, and overall skin quality improvement.